Emergency Node Based Fault Tolerance in Wireless Sensor Networks - Gobinath, T; Tamilarasi, A (International Journal of Engineering and Technology, 2018)
In Wireless Sensor Network (WSN), fault occur due to node failure, malicious attack and link failure. Link failure causes the loss of sensitive data in a network leads to the emergency situation and influence generated and incoming data resulting in high probability of erroneous data, false packet transmission, wrong decision making and rigorous communication interruption. It leads to increase of traffic overhead and faulty node count in the network. In order to avoid this problem Emergency Node(EN) based process is proposed. Simulation clearly shows that the proposed method increased the packet delivery ratio and decreased the average delay, Energy consumption in WSN.